Genome-wide identification and expression analysis of sulfate transporter (SULTR) genes in potato (Solanum tuberosum L.) - ÖZYİĞİT, İBRAHİM İLKER (SPRINGER, 2016)
Solanum tuberosum genome analysis revealed 12 StSULTR genes encoding 18 transcripts. Among genes annotated at group level ( StSULTR I-IV), group III members formed the largest SULTRs-cluster and were potentially involved in biotic/abiotic stress responses via various regulatory factors, and stress and signaling proteins. Employing bioinformatics tools, this study performed genome-wide identification and expression analysis of SULTR (StSULTR) genes in potato (Solanum tuberosum L.). Very strict homology search and subsequent domain verification with Hidden Markov Model revealed 12 StSULTR genes encoding 18 transcripts. StSULTR genes were mapped on seven S. tuberosum chromosomes. Annotation of StSULTR genes was also done as StSULTR I-IV at group level based mainly on the phylogenetic distribution with Arabidopsis SULTRs. Several tandem and segmental duplications were identified between StSULTR genes. Among these duplications, Ka/Ks ratios indicated neutral nature of mutations that might not be causing any selection. Two segmental and one-tandem duplications were calculated to occur around 147.69, 180.80 and 191.00 million years ago (MYA), approximately corresponding to the time of monocot/dicot divergence. Two other segmental duplications were found to occur around 61.23 and 67.83 MYA, which is very close to the origination of monocotyledons. Most cis-regulatory elements in StSULTRs were found associated with major hormones (such as abscisic acid and methyl jasmonate), and defense and stress responsiveness. The cis-element distribution in duplicated gene pairs indicated the contribution of duplication events in conferring the neofunctionalization/s in StSULTR genes. Notably, RNAseq data analyses unveiled expression profiles of StSULTR genes under different stress conditions. In particular, expression profiles of StSULTR III members suggested their involvement in plant stress responses. Additionally, gene co-expression networks of these group members included various regulatory factors, stress and signaling proteins, and housekeeping and some other proteins with unknown functions.
Keywords: Solanaceae; In silico; RNA-Seq; Stress factor; Phytohormones; Solanum tuberosum; R2R3-MYB TRANSCRIPTION FACTORS; COMPUTATIONAL IDENTIFICATION; ARABIDOPSIS-THALIANA; SULFUR ASSIMILATION; RNA-SEQ; PLANT; STRESS; MICRORNAS; PROVIDES; GLUCOSYLTRANSFERASE